Comparative Performance Study of Eight Grasses for their Use in Waterways - Dalal, S. S.; Patnaik, N.; Singh, Dakhshish (Indian Forester, 1965)
Performance of 8 grasses was studied to find their suitability for waterways. Of these, Panicum repens gave best results as it maintained wel1 with a thick sod and high forage yield. Brachiaria mutica and Cynodon plectostachyum are considered next best in their performance. Cynodon dactylon provided excellent protection but its forage yield was comparatively low. Paspalum notatum was slow to establish in the first year and produced lower forage yield although it formed thick matting in subsequent years providing Good protection to waterway. The method of establishing a grassed waterway, as discussed , was used successfully to stabilise waterway in Dhulkot Demonstration Project with Panictum repens and Cyndon plectostachyum.